Thermo‐physical properties of n‐pentane/bitumen and n‐hexane/bitumen mixture systems. (9th June 2017) - Haddadnia, Ali; Zirrahi, Mohsen; Hassanzadeh, Hassan; Abedi, Jalal
Abstract : The gravity drainage as a result of viscosity reduction is the main governing mechanism of the solvent‐aided thermal bitumen recovery processes. Therefore, the density and viscosity of the diluted or heated bitumen are essential to predict the oil production rate. In this paper, we report thermo‐physical properties of n ‐pentane/bitumen and n ‐hexane/bitumen mixtures. The density and viscosity of Athabasca bitumen diluted with n ‐pentane and n ‐hexane were measured at different temperatures (30 to 190 °C), pressures (2 to 8 MPa), and solvent mass fractions (0.05 to 0.5). Various correlations and mixing rules proposed in the literature were examined to calculate the density and viscosity of the diluted bitumen. This study proposes appropriate mixing rules and generalized parameters for predicting the density and viscosity of solvent‐bitumen systems. Our findings will find applications in the design and simulation of heavy oil and bitumen solvent‐aided thermal recovery processes.